PENGARUH LEADER MEMBER-EXCHANGE (LMX) DAN KEADILAN ORGANISASI TERHADAP KOMITMEN BERKELANJUTAN - Dikson Silitonga; Emmi Pasaribu (Lembaga Riset dan Pengabdian Masyarakat Institut Bisnis Nusantara, 2019)
The continuance commitment is assumed to be affected by the variation in the Leadership Member-Exchange (LMX), and organizational justice. The aim of the experimental study reported here was to test the hypothesis. The causal study was conducted on the teacher of Senior High School in the administrative city of Central Jakarta, from May 2014 to January 2015, involving a sample of 207 teachers, who had been selected from 429 teachers in the school by using to proportional random sampling technique. Data of each variable were collected through a survey analyzed descriptively and Inferentially through the path analysis. Result show direct effects of the Leader Member-Exchange (LMX) and organizational justice on their continuance commitment; and Leader Member-Exchange (LMX) on their organizational justice.Keyword: leader member exchange, organizational justice, continuance commitment